Effect of Different Strength of Nutrient Solution on Growth and Yield of Rock Melon in Bangladesh - Yasmin, S.; Rahman, M. J.; Raihan, A.; Chandni, C. S.; Ali, M. S.; Ali, Md. Mokshead; Hossain, M. Mokbul; Sabbir, M. (European Journal of Applied Sciences, 2023)
The experiment was conducted at the Hydroponic Farm of the Horticulture farm is Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to identify suitable strength of nutrient solution to get higher yield in Bangladesh. Two factors were used as treatments in this experiment viz, variety and nutrient solution. Three varieties, viz. V1= Action-434, V2= Madhurima, V3= F1-Hybrid and three nutrient solutions viz. S1=Full strength Rahman and Inden nutrient solution, S2 = 3/4 strength Rahman and Inden nutrient solution, S3 = Full strength of Hoagland and Arnon nutrient solution were used in this experiment. The experiment was conducted in a completely randomized block design with four replications. Different strength of nutrient solutions and different varieties of rock melon showed significant variation in most of the parameters studied. The highest plant height (7.68, 25.60, 37.78, and 54.11 cm) the maximum number of leaves/plant (9.16, 23.91, 31.10 and 50.12), the maximum number of shoots per plant (4.51, 3.56 and 4.39), the maximum number of fruits/plant (4.99), individual fruit weight (1537gm), fruit length (14.78), fruit diameter (52.88cm) and yield per plant (2.48 kg) were found the highest in S2. And also, all the parameters were found the highest in V2. But all the parameters were drastically reduced when S1 treatment was applied and also reduced V1. For combined effects, all the parameters were found the highest in V2S2. Meanwhile all the parameters were reduced V1S1. Therefore, S2 nutrient solution can be used for rock melon cv. Madhurima (V2) in soilless system in Bangladesh.